Raynaud's phenomenon and its impact on activities in daily life during one year of follow-up in early systemic sclerosis. (4th May 2018) - Sandqvist, G; Wollmer, P; Scheja, A; Wildt, M; Hesselstrand, R
Abstract : Objective : To investigate Raynaud's phenomenon (RP) and its impact on daily life activities during 1 year of follow-up in early systemic sclerosis (SSc). Method : Fourteen SSc patients with a median disease duration of 2 years were enrolled in the study. Every 7 weeks the patients completed a 7 day diary documenting the frequency and duration of RP attacks, the activity causing the attack, and how they handled the attack. The patients also recorded in the diary daily self-assessments of the difficulties with RP, using a 0–10 ordinal scale according to the Raynaud's Condition Score. Results : Ninety-eight RP weekly diaries were analysed. The median number of RP attacks varied between six and nine per week, and the median score reflecting the difficulty associated with the attacks varied between 2.0 and 2.9. No difference was found in the number of attacks or the difficulties associated with them between winter, spring, and autumn. Fewer attacks and less difficulty were reported in August than in any of the other documented weeks (p < 0.05). In all diaries, all patients reported RP attacks associated with domestic activities. The use of heating devices varied during the follow-up. In February, all patients except one used such devices, while about half of the group used devices during the rest of the year. Conclusions : Difficulties resulting from RP are present and disabling all year round, which underscore the importance of intense vasoactive therapy and non-pharmacological strategies throughout the year.